Electrosynthesis of Dihydropyrano[4, 3‐b]indoles Based on a Double Oxidative [3+3] Cycloaddition. Issue 29 (18th May 2020) - Choi, Subin; Park, Jinhwi; Yu, Eunsoo; Sim, Jeongwoo; Park, Cheol‐Min
Abstract: Oxidative [3+3] cycloadditions offer an efficient route for six‐membered‐ring formation. This approach has been realized based on an electrochemical oxidative coupling of indoles/enamines with active methylene compounds followed by tandem 6π‐electrocyclization leading to the synthesis of dihydropyrano[4, 3‐ b ]indoles and 2, 3‐dihydrofurans. The radical–radical cross‐coupling of the radical species generated by anodic oxidation combined with the cathodic generation of the base from O2 allows for mild reaction conditions for the synthesis of structurally complex heterocycles. Abstract : Oxidative [3+3] cycloadditions constitute an efficient approach for the generation of six‐membered rings. Such a strategy was realized through an electrochemical oxidative coupling of indoles/enamines with active methylene compounds followed by tandem cyclization to generate dihydropyrano[4, 3‐ b ]indoles and 2, 3‐dihydrofurans.